substitute m/p =v, so now m/p = 4/3pi r^3
flip flop gonip ginop the 4/3pi on the other side of equal sign, but leave behind the cube root radius
3m/4p.pi= r^3
perform cube root canal to get the radius by itself, since that is what they are asking for
(3m/4p.pi)^1/3 = r

## Comments (1)

substitute m/p =v, so now m/p = 4/3pi r^3

flip flop gonip ginop the 4/3pi on the other side of equal sign, but leave behind the cube root radius

3m/4p.pi= r^3

perform cube root canal to get the radius by itself, since that is what they are asking for

(3m/4p.pi)^1/3 = r